The botanical effect of pasturing upon the native grasses - Cooley, Perry Alfred (My University, 1906)
Introduction: The importance of the stock interest in Kansas justifies a thorough and careful study of the pasture grasses, and if possible to improve them or at least to protect what we have. It is a fact that the tame and cultivated grasses have an important place, yet in my estimation they will never replace the natural grasses, especially for resistance, and abundance of feed and on the rocky side hill or dry upland. My observations extended over the three pasturing seasons of 1903, 1904 and 1905, each year over the same group of pastures. These groups contained several thousand acres in each, taking in as many varieties of pasture as possible, and in this respect it would be hard to excel in any other part of the state. The largest group of pastures were the C.P. Dewey range south of Manhattan in Riley and Geary counties, though not as large there were many others in that section. The group I designated as group C. The next group I worked with was north-east of Manhattan in Pottawatomie county, group B. This contained a large variety of pastures, especially the sand. The next and last, group A, was north-west of Manhattan in Riley county, this was practically the same as the south-east, group C. I found that in many instances that the three groups especially the individual pastures in each group, that what was true or one was true of all.
Citation: Cooley, Perry Alfred. The botanical effect of pasturing upon the native grasses. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Pasture; Grasses; Riley County; Pottawatomie County; Kansas; Theses